AKIBAT HUKUM AKTA OTENTIK YANG TERDEGRADASI MENJADI AKTA DIBAWAH TANGAN - Soegeng Ari Soebagyo; Gunarto Gunarto (Jurnal Akta, 2017)
The study entitled "Legal Effects Against the Authentic Deed of Degradation Becoming a Deed of Hands" aims to recognize the legal consequences of the degraded authentic deed and the responsibility of Notary over the degraded authentic deed to become a deed under the hand. This research uses juridical socio legal research approach, in collecting data more emphasized on source of primary material, in the form of legislation, studying law norms and law science sera theory in addition to interviews to the parties related to the problem in carefully. Based on the method, the research produces principally (i) Authentic deeds can be degraded into deeds under the hand when the requirements of the authentic deed are not met, whether material or formal terms which have the authority to judge them is a court. ) What are the legal consequences of an authentic deed that is deemed to be a deed under the hand does not have legal validity as an authentic deed, only a word under the hand that has no legal force to bind this subject under KUHperdata article 1869 and can be seen in Law no. 2 Year 2014 jo. UU no. (3) Article 51 paragraph (4), (iii) The responsibility of a Notary if The authentic deed he made into a deed under the hand, the Notary may be held accountable; (-) Administrative liability If a Notary is found guilty of violating Article 85 of Law Number 30 Year 2004 which regulates the obligation and prohibition for Notary in carrying out his / her position. (-) Accountability according to Civil Law of this matter as Article 1365 Civil Code, and can be seen In Law no. 2 Year 2014 jo. UU no. Article 49 paragraph (3) of Article 49 paragraph (4), Article 50 paragraph (5), Article 51 paragraph (4) (-) Accountability under criminal law if Notary deliberately falsely authentic deed or intentionally include incorrect information in the authentic deed he madeKeywords: Authentic Deed, Notary, Degradation